Os desafios de mulheres influenciadoras digitais do nicho de maternidade: estudo de caso de Dheliane Moriz - Costa, Rita de Cássia Holanda da (Brasil, 2022)
This course conclusion work analyzes the challenges that influencers from the maternity niche go through in their daily lives, reconciling with their multiple tasks. The case study method is used, in which the way in which an influencer behaves in the face of her experience was observed in a holistic way. As an object, the profile of the mother and Amazonian influencer Dheliane Moriz was chosen, who together has more than 123 thousand followers and 1,332 posts in the feed of Instagram, being representative in relation to the starting point of the research. The methodology consisted of a literature review, interview with the participant through a semi-structured questionnaire and analysis of Instagram page posts. As a result, three major challenges were reflected that encompass the experience of influencers in the maternity niche: the multiple workday, the relationship with followers and customers, and child exposure. The research provides a view of the way in which the digital influencer from the maternity niche deals with social pressures regarding being a woman and mother who is receiving positive and negative comments about their lives and raising their daughters every day, in addition to exercising their profession in the digital world and beyond. Thus, it is intended to contribute to the promotion of research on the role of digital influencers, as well as to reflect on ways to improve the well-being of these communication professionals.